An evolution in the management of fractures of the ankle: safety and efficacy of posteromedial approach for Haraguchi type 2 posterior malleolar fractures. (November 2017) - Bali, N.; Aktselis, I.; Ramasamy, A.; Mitchell, S.; Fenton, P.
Abstract : Aims: There has been an evolution recently in the management of unstable fractures of the ankle with a trend towards direct fixation of a posterior malleolar fragment. Within these fractures, Haraguchi type 2 fractures extend medially and often cannot be fixed using a standard posterolateral approach. Our aim was to describe the posteromedial approach to address these fractures and to assess its efficacy and safety. Patients and Methods: We performed a review of 15 patients with a Haraguchi type 2 posterior malleolar fracture which was fixed using a posteromedial approach. Five patients underwent initial temporary spanning external fixation. The outcome was assessed at a median follow-up of 29 months (interquartile range (IQR) 17 to 36) using the Olerud and Molander score and radiographs were assessed for the quality of the reduction. Results: The median Olerud and Molander score was 72 (IQR 70 to 75), representing a good functional outcome. The reduction was anatomical in ten, with a median step of 1.2 mm (IQR 0.9 to 1.85) in the remaining five patients. One patient had parasthaesiae affecting the medial forefoot, which resolved within three months. Conclusion: We found that the posteromedial approach to the ankle for the surgical treatment of Haraguchi type 2 posterior malleolar fractures is a safe technique that enables good visualisation and reduction of the individual fracture fragments with promising early outcomes. Cite this article: Bone Joint J 2017;99-B:1496–1501.